Longitudinal monitoring of CYP3A activity in patients receiving 3 cycles of itraconazole pulse therapy for onychomycosis. (10th January 2014) - Shibata, S.; Takahashi, H.; Ono, N.; Wada, N.; Kubo, H.; Shinozaki, K.; Saito, H.; Inamoto, N.; Machida, M.; Atsuda, K.; Echizen, H.
Summary What is known and objective Itraconazole, a CYP3A inhibitor, is used for the treatment for onychomycosis with a three‐cycle pulse therapy over 3 months, but its effects on in vivo CYP3A activity during the entire course remain unknown. Methods Urinary 6β‐hydroxycortisol/cortisol ratios were determined in 19 patients with onychomycosis, before therapy, during three cycles of itraconazole pulse therapy (200 mg twice daily for a week in each monthly cycle) and at 3 month after completion of therapy. Results and discussion The mean 6β‐hydroxycortisol/cortisol ratio was reduced by 68% from baseline (P < 0·05) after the 1st pulse dosing, but the inhibitory effect appeared to be resolved before the next pulse dosing and at 3 months post‐treatment. The magnitude of inhibition appeared in proportion to the baseline CYP3A activity. What is new and conclusion The inhibitory effect of itraconazole pulse therapy on the in vivo CYP3A activity appears clinically relevant at the end of each cycle, but the inhibition resolves, on average, within 3 weeks.